Origin of the planting material and its influence on the rapid propagation method of cassava - Porto, Marcio Carvalho Marques; Carvalho, José Eduardo Borges de; Manos, Pedro Luiz Pires de; Macedo, Manuel Claudio Moita (Pesquisa Agropecuaria Brasileira, 2014)
A study was carried out in order to determine the influence of cuttings from different parts of the main stem (basal, medium and apical) of two cassava cultivars (Manihot esculenta Crantz), on their germination and number of sprouts. The experimental design was the split-plot with five replications. The best results were obtained with the medium and basal cuttings, but even the apical ones could be used in substitution for the usual method. There was no significant difference between the cultivars used.